2016
DOI: 10.2147/ott.s126401
|View full text |Cite
|
Sign up to set email alerts
|

Low <em>PLCE1</em> levels are correlated with poor prognosis in hepatocellular carcinoma

Abstract: BackgroundPrevious reports show that phospholipase C epsilon-1 (PLCE1) expression is positively correlated with esophageal squamous cell carcinoma and gastric cardia adenocarcinomas; however, the expression of PLCE1 in hepatocellular carcinoma (HCC) and its correlation with clinical outcome still remain unclear. The aim of this study was to explore the expression of PLCE1 in HCC tissue and to determine whether PLCE1 was a prognostic factor for HCC patients.Materials and methodsPLCE1 levels in 20 paired HCC tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…THBS1 increase may inhibit angiogenesis and stimulate apoptosis during WWOX or AP-2α overexpression, contrary to AP-2γ which downregulates this gene. A similar finding applies to PLCE1 which prevents the tumor invasion [52]; it is increased during WWOX overexpression but not when AP-2γ is at a high level. Through Ca 2+ -dependent signaling, PLCE1 affects NFATC1 which further regulates SERINC5.…”
Section: Discussionmentioning
confidence: 54%
“…THBS1 increase may inhibit angiogenesis and stimulate apoptosis during WWOX or AP-2α overexpression, contrary to AP-2γ which downregulates this gene. A similar finding applies to PLCE1 which prevents the tumor invasion [52]; it is increased during WWOX overexpression but not when AP-2γ is at a high level. Through Ca 2+ -dependent signaling, PLCE1 affects NFATC1 which further regulates SERINC5.…”
Section: Discussionmentioning
confidence: 54%
“…It interacts with the proto-oncogene Ras among other proteins ( Bunney et al, 2009 ). The expression of PLCE1 was significantly related to tumor differentiation degree, invasion depth, lymph node metastasis and distant metastasis ( Cui et al, 2014b ; Cheng et al, 2017 ; Yu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These articles show that PLCE1 is highly expressed in tumor tissues, including bladder cancer, renal cell cancer, NSCLC, and ESCC, which is consistent with our findings. However, Cheng, Xing, Jia, Huang, and Bian (2017) showed that PLCE1 expression at the mRNA and protein levels was decreased compared with non‐HCC tissues. Among these research concerning PLCE1 expression with tumors, only Nana Bian et al indicated a low expression of PLCE1 in tumors, which is not consistent with the above studies—PLCE1 is highly expressed (or overexpression) in tumors.…”
Section: Discussionmentioning
confidence: 99%